La Culture est l'Inversion de la Vie. (1st December 2015) - Memou, Antigoni
Constructed Situations: A New History of the Situationist International, Frances Stracey (2014) London: Pluto, 200 pp., ISBN: 9780745335261, p/bk, £15.00